2017
DOI: 10.1123/rsj.2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Recreation Center Utilization Affects Academic Outcomes

Abstract: This study described the association between students' use of a university recreation center and concomitant achieved cumulative grade point average (GPA). Data were derived retrospectively from undergraduate student records from 12 consecutive months ( N = 6,098). Results showed that in general, use of the recreation center on campus was beneficial to a student's academic performance, where female students who visited the facility more often had higher GPAs on average. When GPAs were considered categorically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…While there has been advancement in characterizing the relationship between CR usage and academic performance, conclusions remain limited due to a variety of factors. Such factors include the absence of an adequate control group of nonusers (Roddy et al, 2017), lack of appropriate confounder adjustment (Danbert et al, 2014), and a dearth of longitudinal data to support the relationship between physical activity and academic outcomes (Brock et al, 2015). Therefore, the purpose of this study was to extend examination of the relationship between usage of CR facilities and academic achievement metrics by accounting for a variety of sociodemographic factors that have not been examined before, including student status (FTIC or non-degree seeking), academic class level, gender, race/ethnicity, college affiliation, and age group.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been advancement in characterizing the relationship between CR usage and academic performance, conclusions remain limited due to a variety of factors. Such factors include the absence of an adequate control group of nonusers (Roddy et al, 2017), lack of appropriate confounder adjustment (Danbert et al, 2014), and a dearth of longitudinal data to support the relationship between physical activity and academic outcomes (Brock et al, 2015). Therefore, the purpose of this study was to extend examination of the relationship between usage of CR facilities and academic achievement metrics by accounting for a variety of sociodemographic factors that have not been examined before, including student status (FTIC or non-degree seeking), academic class level, gender, race/ethnicity, college affiliation, and age group.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence supports that greater student involvement leads to better freshman adjustment and retention (Friedlander et al, 2007;Huesman et al, 2009;Kuh et al, 2008;Melendez, 2007;Tieu & Pancer, 2009;Tieu et al, 2010), selfesteem improvements (Carruthers et al, 2010;Friedlander et al, 2007;Tieu & Pancer, 2009;Tieu et al, 2010), stress reduction (Beiter et al, 2015;Thompson et al, 2013;Tieu & Pancer, 2009;Tieu et al, 2010;VanKim & Nelson, 2013;Weinstein & Laverghetta, 2009) and career success (Clark et al, 2015;Hall-Yannessa & Forrester, 2004;Tchibozo, 2007;Thompson et al, 2013). It is important to recognize that quality of involvement matters more than quantity (Tchibozo, 2007;Tieu & Pancer, 2009;Tieu et al, 2010), and that students can become over-involved in one or more activities to the detriment of other areas of their student life (Gardner et al, 2010;Koehler, 2014;Linnemeyer & Brown, 2010;Roddy et al, 2017).…”
mentioning
confidence: 99%
“…National Collegiate Athletic Association or National Association of Intercollegiate Athletics) level, provide students opportunities for socialization and leadership, creating community identity within their institution, and engaging in vigorous physical activity for the associated physical and mental health benefits (Chen et al, 2010;Chu & Zhang, 2018;Gould & Carson, 2008;Hall-Yannessa & Forrester, 2004;Lower-Hoppe, Beattie, et al, 2020;Melendez, 2007;Mikulec & McKinney, 2014;VanKim & Nelson, 2013). College sport participation provides documented added value to academic achievement compared to non-athlete students, such as better academic adjustment (Melendez, 2007), better retention rates (Forrester et al, 2018;Kiss, 2017), higher grade point averages (GPAs) (Roddy et al, 2017;Vasold et al, 2019), and higher graduation rates (National Collegiate Athletic Association, 2017; U.S. Department of Education, 2017). However, sports participation creates stresses that may interfere with the academic gains of students, including time commitments to practices, games, and team meetings; physical and mental fatigue; and both selfimposed and external pressures to excel in sports performance (Henderson, 2013;Lower et al, 2013).…”
mentioning
confidence: 99%
“…Academic achievement has been examined as one of the important benefits of the use of CRCs. Many scholars have examined the relationship between the utilization of CRCs and academic achievements of students (Todd et al, 2009;Huesman, Brown, Lee, Kellogg, & Radcliffe, 2007;Roddy, Pohle-Krauza, & Geltz, 2017). Todd and colleagues (2009) investigated student academic performance based on the frequency of CRC visits through the quantitative method.…”
Section: Campus Recreation Center (Crc)mentioning
confidence: 99%
“…Other benefits found from using campus recreation programs include improved academic performance (Todd, Czyszczon, Carr, & Pratt, 2009), social interactions (Henchy, 2011), and school retention (Lindsey & Sessoms, 2006;Kampf & Teske, 2013). The study of Roddy et al (2017) also revealed data on gender differences in response to CRCs, where female students who utilized these facilities more often had higher GPAs on average than those who didn't.…”
mentioning
confidence: 99%